If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 95 + -7x = 29x + 19 Reorder the terms: 95 + -7x = 19 + 29x Solving 95 + -7x = 19 + 29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29x' to each side of the equation. 95 + -7x + -29x = 19 + 29x + -29x Combine like terms: -7x + -29x = -36x 95 + -36x = 19 + 29x + -29x Combine like terms: 29x + -29x = 0 95 + -36x = 19 + 0 95 + -36x = 19 Add '-95' to each side of the equation. 95 + -95 + -36x = 19 + -95 Combine like terms: 95 + -95 = 0 0 + -36x = 19 + -95 -36x = 19 + -95 Combine like terms: 19 + -95 = -76 -36x = -76 Divide each side by '-36'. x = 2.111111111 Simplifying x = 2.111111111
| 10-6c=-5c-2 | | 5-6s=-7 | | 3x+12x=10-8x | | 78-5x=10x+28 | | 3-4u=-17 | | 107-7x=38x+22 | | x=x^3 | | -4x-3=21 | | 2x+3y+4x+5y= | | 7-8x=57-22x | | 6+8x=27+x | | -5x+1=21 | | 65-5x=4x+22 | | 8m+8n= | | 5x*2+11=0 | | -5+1=21 | | 5x-3=15x-113 | | 14-9x=109-44x | | 6x+32=13x-45 | | 10x-4=-4 | | 5x+14=-56-9x | | 6x+10=106-6x | | 152-6x=5x+9 | | 6y+7h-2y+3h= | | -34-2x=8-8x | | 87-4x=3x+10 | | x^2+x+.75=0 | | 3(x-7)=19-x | | 4x+13=113-6x | | 1x+13=113-6x | | 3x^3-3x^2+x-1=0 | | 4x+12=64 |